2016
DOI: 10.1016/j.biocontrol.2016.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Gut content analysis of arthropod predators of codling moth in Washington apple orchards

Abstract: Codling moth, Cydia pomonella (L.), is the key pest of pome fruits in many temperate areas of North America, Eurasia, South Africa, South America and Australia. Many predatory arthropods species are found in organic apple orchards of central Washington; here we use PCR-based gut content analysis of arthropod predators to identify predators that attack codling moth. Predators were sampled from tree canopies, tree trunks and from the understory and were homogenized in a lysis buffer to provide a template for dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 67 publications
(76 reference statements)
0
21
0
Order By: Relevance
“…In a recent paper Unruh et al (2016) Yet, the question of the time it takes for prey DNA to travel through the digestive 281 tract of insects and how this varies across different taxa remains. Having a better 282 understanding about the temporal aspects of digestion in insects in general, and 283 particularly in carabid beetles is important.…”
Section: Discussion 228mentioning
confidence: 99%
“…In a recent paper Unruh et al (2016) Yet, the question of the time it takes for prey DNA to travel through the digestive 281 tract of insects and how this varies across different taxa remains. Having a better 282 understanding about the temporal aspects of digestion in insects in general, and 283 particularly in carabid beetles is important.…”
Section: Discussion 228mentioning
confidence: 99%
“…Soon after, entomologists started using various PCR based techniques to accurately screen predator species on specific pest taxa using molecular gut content analysis (King et al, 2008). Several species-specific primers for important pest taxa, such as Colorado potato beetle, Leptinotarsa decemlineata Say 1824 (Coleoptera: Chrysomelidae) , rape pollen beetles, Meligethes aeneus (Fabricius, 1775) (Coleoptera: Nitidulidae) (Oberg et al, 2011), codling moth, Cydia pomonella (Linnaeus, 1758) (Lepidoptera: Tortricidae) (Unruh et al, 2016), flea beetles, Phyllotreta spp. (Coleoptera: Chrysomelidae) (Ekbom et al, 2014), cereal aphid, Rhopalosiphum spp.…”
Section: Use Of Molecular Gut Content Analysis For Identification Of mentioning
confidence: 99%
“…While codling moth is the key pest common to apple, pear, and walnut systems in the western U.S., our investigations focused on predation in apple orchards in Washington State as a representative system. Molecular gut content analysis showed that earwigs, spiders and carabid beetles were responsible for most of the predation events recorded (Unruh et al, 2016). Based on the information generated in this component of the project we can now prioritize conservation efforts for the natural enemies of codling moth, in addition to those of secondary pests, as our IPM programs evolve.…”
Section: Evaluating the Importance Of Codling Moth Predationmentioning
confidence: 96%